Liver Cirrhosis in Woman with Ciliopathy Syndrome - Syifa Mustika; Dian Hasanah (Interna Publishing, 2022)
Ciliopathy syndrome is a congenital abnormality of structure and/or function of cilia, which causes pleiotropic disorder, including liver cirrhosis. This study aimed to describe a unique case of liver cirrhosis with possible aetiology of ciliopathy syndrome. A 44 year-old woman with chief complain of hematemesis had diabetes mellitus, obesity, dyslipidaemia, amenorrhoea and often became unconscious. We found short stature, brachydactyly, hyperpigmented maculae in trunk and four limbs, and hepatosplenomegaly. The laboratory results showed: haemoglobin 7.4 g/dl; albumin 2.42 g/dl; urea 84.8 mg/dl; creatinine 2.4 mg/dl; prolactin 138.8 ng/ml, while HBsAg was negative and anti-HCV was non-reactive. Abdominal ultrasonography showed liver cirrhosis; endoscopy showed grade 3 oesophageal varicose; FibroScan showed 75 kPa; liver biopsy showed hydropic degeneration and cirrhosis; and head CT scan showed chronic lacunar infarction of corona radiata and mega cisterna magna occipital. We reported female with oesophageal varicose rupture, short stature, brachydactyly, obesity, diabetes mellitus, dyslipidaemia, hyperpigmented maculae, liver cirrhosis and mega cisterna magna, which was likely to suffer from ciliopathy syndrome.